A Fluorescent Reporter Virus Toolkit for Interrogating Enterovirus Biology and Host Interactions - Mireya Martínez-Pérez; Sebastian Velandia-Álvarez; Cristina Vidal-Verdú; Beatriz Álvarez-Rodríguez; Ron Geller (Viruses, 2025)
Enteroviruses are a group of highly prevalent human pathogens responsible for a wide range of illnesses, ranging from common cold symptoms to life-threatening diseases. A deep understanding of enterovirus biology, evolution, and host interaction is required for the development of effective vaccines and antivirals. Recombinant reporter viruses encoding luminescent or fluorescent proteins have been developed to facilitate such investigation. In this work, using coxsackievirus B3 as our model, we analyze how the insertion of fluorescent reporter genes at three distinct sites within the viral polyprotein affects viral fitness, identifying the most tolerant site for reporter insertion. We then describe a set of experimental workflows for measuring viral fitness, sera neutralization, antiviral efficacy, and recombination using fluorescent reporter viruses. The high homology between different enteroviruses suggests these assays can be readily adapted to study additional members of this medically and economically relevant group of viruses.